STUDI ANALISIS PESAN DAKWAH DALAM FILM ANIMASI IBRA PADA EPISODE 10 FOMO: Perspektif Semiotika Ferdinand de Saussure - Luthfi Hidayah; Khofifah Nur Lailah (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2024)
Da'wah of Islam develops over time. The elements, materials, and means of da'wah have also developed. Da'wah media are increasingly diverse, including YouTube which allows broadcasts in minutes. Dakwah content on YouTube is an option as entertainment, education and information to replace TV programs that are not always in accordance with religious values. Thus, the animated film Ibra appeared, made by Indonesian children, which raised the Islamic message and the story of the Prophet Muhammad, and gave teachings to all ages. Researchers are interested in Ibra's animated film, especially in episode 10: FOMO on his YouTube account, Ibra Berkisah, because in that episode FOMO is significant in various aspects of Indonesian society: social media, education, social, consumption, religion and can affect behavior change, especially young generation. This study uses qualitative methods with a focus on literature review and a descriptive approach. The human instrument method is also used to determine focus, select relevant data sources, collect, evaluate, analyze, interpret data, and draw conclusions. The researcher analyzed the animated film Ibra episode 10 using the Ferdinand de Saussure Semiotics approach, using visual and audio data as sources. The main objective is to understand and analyze the da'wah messages contained in the animation. The analysis results of Ibra's animation episode 10 FOMO reveal the concept of da'wah conveyed through moral messages and religious values. The delivery of these Islamic values ​​takes the form of stories with moral messages, an introduction to religious teachings, as well as motivation and inspiration that are packaged in a fun and easy-to-understand way, especially for children and adolescents. Semiotic signs, such as linguistic, visual, sound, movement, and expression, strengthen da'wah messages emotionally and cognitively. The results of the analysis in each scene contain various messages that teach mutual forgiveness, the importance of knowledge, tolerance, respect for differences, the dangers of FOMO, and holding on to the truth even when faced with hostility.